The Effect of Financial Performance on Stock Prices in Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange - Riyan, Riyan Dika Pratama; Dika Pratama, Riyan; Setiawan sapitra, Ade; Rasita, Elya (International Forum of Researchers and Lecturers, 2025)
Using the Systematic Literature Review (SLR) method, the purpose of this study is to investigate the effect of financial performance on the stock prices of food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The financial performance factors analyzed include Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Return on Investment (ROI). Data were collected from fifteen nationally accredited scientific articles published during the period and were eligible for inclusion. The results show that Return on Assets (ROA) consistently has a positive effect on stock prices, making it the most important indicator to attract investors. Since investors prioritize profitability over short-term liquidity, Current Ratio (CR) is usually not very influential. Debt to Equity Ratio (DER) results vary depending on the debt condition of companies and their financial plans. However, Return on Investment (ROI), which has not been studied much, seems to have a significant impact on stock prices and is starting to attract the attention of investors in the food and beverage industry. This study helps by providing a comprehensive picture of the pattern of influence of financial ratios on stock prices and complements the shortcomings of current research, especially regarding the ROI variable which is still minimal in previous studies. It is hoped that these findings will help investors, company management, academics, and regulators make decisions and create investment strategies in the Indonesian capital market.